Breakthroughs in Photonics 2009 (IEEE Photonics Journal)
"Breakthroughs in Photonics" is intended to highlight major accomplishments across the broad spectrum of Photonics Science and Technology within the year. This Special Section is also intended to draw the attention of readers and authors to the topics that are within the scope of the journal. "Breakthroughs in Photonics 2009" contains 17 invited peer-reviewed briefs written by worldrenowned experts. These briefs cover progress in the areas of Coherent Photon Sources, Ultrafast Photonics, Nonlinear Photonics, Terahertz Photonics, Nano-Photonics, Silicon Photonics, Bio-Photonics, Magneto-Photonics, Photonic Materials and Engineered Nanostructures, Photovoltaics and Sensors, and Integrated Photonics Systems. These selected topics represent a subset of the much broader and intense activity in the generation, control, and utilization of radiation that takes place worldwide.